Comparison of histological procedures and antigenicity of human post-mortem brains fixed with solutions used in gross anatomy laboratories - Frigon, Eve-Marie; Gérin-Lajoie, Amy; Dadar, Mahsa; Boire, Denis; Maranzano, Josefina (Frontiers in Neuroanatomy, 2024)
Background: Brain banks provide small tissue samples to researchers, while gross anatomy laboratories could provide larger samples, including complete brains to neuroscientists. However, they are preserved with solutions appropriate for gross-dissection, different from the classic neutralbuffered formalin (NBF) used in brain banks. Our previous work in mice showed that two grossanatomy laboratory solutions, a saturated-salt-solution (SSS) and an alcohol-formaldehyde-solution (AFS), preserve antigenicity of the main cellular markers (neurons, astrocytes, microglia, and myelin). Our goal is now to compare the quality of histology and antigenicity preservation of human brains fixed with NBF by immersion (practice of brain banks) vs. those fixed with a SSS and an AFS by whole body perfusion, practice of gross-anatomy laboratories.We used a convenience sample of 42 brains (31 males, 11 females; 25-90 years old) fixed with NBF (N=12), SSS (N=13), and AFS (N=17). One cm 3 tissue blocks were cut, cryoprotected, frozen and sliced into 40 µm sections. The four cell populations were labeled using immunohistochemistry (Neurons=neuronal-nuclei=NeuN, astrocytes=glial-fibrillary-acidic-protein=GFAP, microglia=ionized-calcium-binding-adaptor-molecule1=Iba1 and oligodendrocytes=myelin-proteolipid-protein=PLP). We qualitatively assessed antigenicity and cell distribution, and compared the ease of manipulation of the sections, the microscopic tissue quality, and the quality of common histochemical stains (e.g., Cresyl violet, Luxol fast blue, etc.) across solutions.Results: Sections of SSS-fixed brains were more difficult to manipulate and showed poorer tissue quality than those from brains fixed with the other solutions. The four antigens were preserved, and cell labeling was more often homogeneous in AFS-fixed specimens. NeuN and GFAP were not always present in NBF and SSS samples. Some antigens were heterogeneously distributed in some specimens, independently of the fixative, but an antigen retrieval protocol successfully recovered them. Finally, the histochemical stains were of sufficient quality regardless of the fixative, although neurons were more often paler in SSS-fixed specimens. Conclusion: Antigenicity was preserved in human brains fixed with solutions used in human grossanatomy (albeit the poorer quality of SSS-fixed specimens). For some specific variables, histology quality was superior in AFS-fixed brains. Furthermore, we show the feasibility of frequently used histochemical stains. These results are promising for neuroscientists interested in using brain specimens from anatomy laboratories.